ГОЛЫШЕВИТ (NAСA)10CA9(FE3+,FE)2ZR3NBSI25O72(CO3)(OH3) Н2О И МОГОВИДИТ, NА9(СА,NА)6СА6(FЕ3+,РЕ2+)2ZN3⁬SI25О72(СО3)(ОН,Н2О)4 - НОВЫЕ МИНЕРАЛЫ ГРУППЫ ЭВДИАЛИТА ИЗ ВЫСОКОКАЛЬЦИЕВЫХ АГПАИТОВЫХ ПЕГМАТИТОВ КОВДОРСКОГО МАССИВА, КОЛЬСКИЙ ПОЛУОСТРОВ - Чуканов Н.В.; Моисеев М.М.; Расцветаева Р.К.; Розенберг К.А.; Задов А.Е.; Пеков И.В.; Коовушкин В.В. (My University, 2005)
New cudialyte-group minerals, golyshevite and mogovidite, have been discovered in calcium-rich peralkalinc pegmatites in Kovdor massif, Kola peninsula, Russia. Golvshevitc is associated with cancrinite, aegirinc-augitc, hedenbcrgitc, orthoclasc, pectolite, thomsonitc-Ca, tacharanitc, calcite, mogovidite - with ncphclinc, aegirine-augite, pectolite, zircon, titanitc, humite, andradite, scolecite, calcite. Golyshcvite was named after crys-tallographcr Vladimir Mikhailovich Golyshev (1943-2000) from the Mordvinian State University, Saransk, Russia, mogovidite - for the Mountain Mogo-Vid near the mineral locality. The new minerals form brown to reddish-brown grains up to 2 cm in size and, rarely, crystals with main forms {0001}, {1011} and {0112}; brittle, Mobs' hardness 5'/2- Golyshcvite has non-perfect cleavage on {0001}. Both minerals are uniaxial, optically negative. For golyshcvitc, ш = 1.628(1), e = 1.618(2), £>meas = 2.89(1) g/cm3 (volumetric method); Dcalc = 2.889 g/cm3. For mogovidite, ш = 1.618(1), e = 1.611(2), Z)meas = 2.90(1) g/cm3 (volumetric method); Z)caic = 2.908 g/cm3. The IR, Mossbauer and thcrmogravimctrical data are given. Crystal structures have been studied. Both new minerals are trigonal space group R3m; for golyshevite, a = 14.231(3), с = 29.984(8) A; for mogovidite, a = 14.232(3), с = = 30.210(3). Unlike eudialyte, in golyshevite Ca prevails in two sites: M(l) andN(4). In mogovidite, Ca prevails in three sites: M(l), N(3) and N(4). Specific mogovidite feature is also the vacant M(3) site. The strongest lines of the powder diffraction pattern [d, A (/, %) (hkt)} are - golyshevite: 4.30(53)(205), 3.200(46)(208), 2.971(78)(315,135), 2.848(100)(404), 2.597(43)(143), 2.055(51)(3.2.10, 2.3.10); mogovidite: 4.31(64)(205), 3.213(100)(208,306, 036), 3.027(65)(119,119,042), 2.977(91)(315,135), 2.859(79)(404). Chemical compositions of golyshevite and mogovidite are respectively (wt %, electron probe, H2O content - by Penfield method, CC>2 - by selection sorption, valency of Fe - from the Mossbauer data): N32O9.19 and 9.78; K2O 0.46 and 0.36; CaO 17.24 and 18.03; MnO 0.69 and 0.68; FeO 1.19 and 1.32; Fe2O3 4.44 and 3.78; A12O3 0.14 and 0; La2O3 0.15 and0.15; Ce2O3 0.29 and0.28; SiO2 48.74 and 47.49; TiO2 0 and 0.23; ZrO2 12.03 andll.90;Nb2O52.63 and 1.72; C10.24 and 0.52; H2O 1.30 and 1.25; CO2 1.52 and 1.45;-O=C12-0.05 and -0.12; total 100.20 and 98.82. Empirical formulae are (Z= 3): (Na9 02Ca0 43Ko 30)i;9 75 (Cas92CeoosLao03)2:600 Рс?+69РсЙоМп0.29 Zr2.97(Nbo.6oSio.66Alo.o8)Si24072(OH)2.37(C03)!.05Cl0.2i-l-01H2O (golyshevite), and (Na9.87Ca4.05^-0.24 Се0.обЬао.оз)114.25Са6 ooFe^gFeQ^gMno 3qZr3 02Ti0.o9(Nb0.4oSio.7i)Si24O72(OH)2 86 (CO3)i.o3Cl0.46 0.74H2O (mogovidite). Type material is deposited in Fersman Mineralogical Museum of Russian Academy of Sciences, Moscow (registration numbers: golyshcvitc - 3220/1; mogovidite - 3221/1; 3290/1).
Keywords: 549.657+548.6